2022
DOI: 10.3389/fnagi.2022.821866
|View full text |Cite
|
Sign up to set email alerts
|

Perspectives on the complex links between depression and dementia

Abstract: This review highlights that depression is a growing health problem for the individual, and because of its high frequency in most societies, a growing burden on health care budgets. The focus of the review is the physiological links between depression and dementia, specifically Alzheimer’s disease. It suggests that depression is a significant risk factor for cognitive decline and explores the pathways that may lead depressed individuals to suffer this outcome. This review shows that depression and a number of i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 79 publications
0
14
0
Order By: Relevance
“…Increased Aβ in the CNS can trigger a chronic inflammatory response, which is closely linked to the activation of glial cells and the production of pro-inflammatory cytokines, 33 both contributing to the pathophysiology of depression. 6 This disturbance in intracellular signalling pathways and interference with calcium homeostasis in nerve cells causes adverse effects on synaptic function, 34 considerably involved in depression. 19 The accumulation of Aβ impairs communication between neurons at synapses, resulting in dysfunctions in neurotransmission.…”
Section: Amyloid β Protein Signalling Pathways and Neurotransmissionmentioning
confidence: 99%
See 2 more Smart Citations
“…Increased Aβ in the CNS can trigger a chronic inflammatory response, which is closely linked to the activation of glial cells and the production of pro-inflammatory cytokines, 33 both contributing to the pathophysiology of depression. 6 This disturbance in intracellular signalling pathways and interference with calcium homeostasis in nerve cells causes adverse effects on synaptic function, 34 considerably involved in depression. 19 The accumulation of Aβ impairs communication between neurons at synapses, resulting in dysfunctions in neurotransmission.…”
Section: Amyloid β Protein Signalling Pathways and Neurotransmissionmentioning
confidence: 99%
“…Among the biological changes are vascular diseases, dysfunctions in the hypothalamic-pituitary-adrenal (HPA) axis, dysregulating glucocorticoid hormones, hippocampal atrophy, accumulation of β-amyloid plaques, inflammatory changes and deficiencies in neural growth factors. 6 These connections may help clarify the complex relationship between these two clinical conditions. AD pathology is characterized by the accumulation of β-amyloid and tubulin-associated unit (TAU) proteins, constituting the main components of senile plaques and neurofibrillary tangles (NFTs), respectively.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, sustained exposure to pro-inflammatory cytokines can alter the microglial function and the expression of enzymes responsible for amyloid peptide metabolism, aggravating the pathological process in both depression and dementia (Carrera-González et al 2022 ). In addition, activated pro-inflammatory mediators in depressed individuals have been shown to lead to CSVD with the consequent reduction in CBF, which is known to precede cognitive decline (Hakim 2022 ). On the other hand, recent studies in patients with LLD showed that at baseline, circulating cytokines were low and similar to healthy controls and did not change significantly after treatment with antidepressants or placebos though depression improved after non-placebo treatment.…”
Section: Pathogenic Factors In Lldmentioning
confidence: 99%
“…A recent review stated that there is an association between depression and AD, but more appropriately as a risk factor and not as a predictor or clinical marker of the development of AD (González Hernández et al 2022 ). Several pathways connecting LLD and dementia/AD have been discussed (Guo et al 2022 ; Hakim 2022 ; Harerimana et al 2022 ; Lee et al 2021 ; Linnemann and Lang 2020 ; Mendez 2021 ; Ni et al 2018 ; Ye et al 2016 ; Zhang et al 2022 ; Mendes-Silva et al 2016 ), and there are overlaps between depression and symptoms of AD, although different depressive symptoms in AD may have different etiology (Amidfar et al 2023 ; Novais and Starkstein 2015 ). However, despite extensive clinical, neuroimaging, and neuropathological studies, the pathophysiology and molecular basis of LLD are still poorly understood (Disabato and Sheline 2012 ; Jellinger 2013 , 2022a , b ; Kuo et al 2021 ; Saberi et al 2022 ).…”
Section: Introductionmentioning
confidence: 99%